Cultural Management In Service Innovation: Study Of Public Organizations In Gowa Regency (Journal of Namibian Studies : History Politics Culture, 2023)
This research investigates the relationship between cultural management and innovation in public services in Gowa Regency. This research uses qualitative methods. Through semi-structured interviews and document analysis, this research reveals that cultural management that supports innovation plays a central role in stimulating innovative ideas in public organizations. A culture that is open, collaborative, and supportive of risk-taking tends to create an environment conducive to the development of innovation. The findings also show the important role of leaders in shaping an innovation culture. Leaders who encourage innovation and promote an open culture tend to create an environment that is more supportive of change and innovative development. In addition, the research results emphasize the need for collaboration and active participation in innovation development. Successful innovation in public services often requires contributions from various parties, including members of the organization and the community.